Hebrides - May, Peter, 1951- (Quercus, 2015)
"Peter May and photographer David Wilson present a photographic record of the countless locations around the Hebridean archipelago that so inspired May when he was bringing the islands of detective Fin McLeod's childhood to the page. From the tiny southern island of Barra to the largest and most northern island of Lewis, travel the storm-whipped North Atlantic scenery with May as he once again strolls the wild and breathtaking countryside that gave birth to his masterful trilogy of novels,"--Amazon.com.